Pengaruh Supervisi Kepala Sekolah, Kompensasi, Dan Motivasi Kerja Terhadap Kinerja Guru Sekolah Dasar Di Timor Leste - Barros Calvario, Maria De Fatima; Hadiyati, Ernani; Naser, Jamal Abd (Arthavidya Jurnal Ilmiah Ekonomi, 2018)
Abstract: Improving the quality of education is a development target in the field of national education and is an integral part of efforts to improve human quality in East Timor. For that the teacher as the agent of learning is required to be able to carry out the learning process as well as possible. This study aims to explain: (1) The influence of school principal supervision, compensation, and motivation together on teacher performance. (2) The influence of the principal's supervision on teacher performance. (3) Effect of work compensation on teacher performance. (4) Effect of work motivation on teacher performance. (5) The most variable contributes between the principal's supervision, compensation, and work motivation on teacher performance. This research method explains that the research location was conducted at Akanuno elementary school, Motakiik elementary school and Hera primary school in East Timor. The type of research used is explanatory research with a quantitative approach. Variables in this study include school principal supervision, compensation, work motivation, and teacher performance. The population of this study were all Akanuno elementary school teachers, Motakiik elementary school, and Hera elementary school. The sample used was 45 respondents consisting of all elementary school teachers from 15 teachers, Motakiik elementary school 15 teachers and Hera elementary school 15 teachers, so that a total of 45 primary school teachers matched the research criteria and data collection methods using questionnaires. The analysis used is multiple linear regression analysis. The results showed that: (1) Supervision of principals, compensation, and work motivation together had a positive and significant effect on teacher performance. (2) Supervision of school principals has a positive and significant effect on teacher performance. (3) Compensation has a positive and significant effect on teacher performance. (4) Work motivation has a positive and significant effect on teacher performance. (5) Work motivation is proven to contribute the most to teacher performance.Keywords: Principal Supervision, Compensation, Work Motivation, Teacher Performance.